Pendampingan Perawatan Kecantikan Ibu-Ibu Rumah Tangga dI Desa Terjan Kragan Rembang - Erly Juliyani; Musbikhin Musbikhin; Siswadi Siswadi; Muhimmatul Hasanah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2021)
Caring for beauty for every woman is an activity that is almost certainly done every day. These activities are part of being confident in every appearance. In fact, most of the young women and housewives know about facial care or better known as makeup, which is obtained from experience from friends, or seeing in the mass media. The assistance provided to mothers and adolescents in the village of Terjan Kragan Rembang has provided an understanding and change in the creativity of makeup and self-care for daily life. Understanding makeup is not just taking care of the face, or beautifying yourself but also as part of a creative effort to open a new business in the beauty salon field. Assistance activities in beauty care through training have had a positive effect on a better and more harmonious household life in family life. The use of natural ingredients obtained from the daily environment has been part of traditional beauty treatments since our ancestors were preserved.